2018
DOI: 10.1021/acs.est.7b04983
|View full text |Cite
|
Sign up to set email alerts
|

Production Temperature Effects on the Structure of Hydrochar-Derived Dissolved Organic Matter and Associated Toxicity

Abstract: Hydrochar is a carbonaceous material derived from hydrothermal liquefaction, and it carries good potential as a new material for environmental applications. However, little is known about the dissolved organic matter (DOM) associated with hydrochar and the consequences of its release. The relationship between the production temperature and the characteristics of DOM released from hydrochar as well as the associated biotoxicity was investigated using a suite of advanced molecular and spectroscopic tools. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(32 citation statements)
references
References 55 publications
0
32
0
Order By: Relevance
“…Previous research has pointed to the potential presence of some problematic substances including polycyclic aromatic hydrocarbons (PAHs) (Keiluweit et al, 2012;Zhao et al, 2020), heavy metals and other elements (such as Cd, Pb, Cu, Zn, and As) (Freddo et al, 2012;Stefaniuk et al, 2016), water dissolved organic matters (WDOMs) (Smith et al, 2016;Ghidotti et al, 2017) and persistent free radicals (Liao et al, 2014;Lieke et al, 2018). Consequently, a series of studies have been performed on the effects of such hazardous chemicals since they can induce biotoxicity inhibiting germination, causing tissue damage and cytotoxicity (Oleszczuk et al, 2013;Sigmund et al, 2017;Hao et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has pointed to the potential presence of some problematic substances including polycyclic aromatic hydrocarbons (PAHs) (Keiluweit et al, 2012;Zhao et al, 2020), heavy metals and other elements (such as Cd, Pb, Cu, Zn, and As) (Freddo et al, 2012;Stefaniuk et al, 2016), water dissolved organic matters (WDOMs) (Smith et al, 2016;Ghidotti et al, 2017) and persistent free radicals (Liao et al, 2014;Lieke et al, 2018). Consequently, a series of studies have been performed on the effects of such hazardous chemicals since they can induce biotoxicity inhibiting germination, causing tissue damage and cytotoxicity (Oleszczuk et al, 2013;Sigmund et al, 2017;Hao et al, 2018;Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, pyrolysis above 700°C induces a drastic decline of biomethane promotion. These ndings may be explained by changes of molecular structure with temperature (Hao et al, 2018). Indeed, Keiluweit et al (2010) observed a gradual change in the molecular structure of plant biomass-derived biochar with temperature.…”
Section: Effect Of Pyrolysis Temperaturementioning
confidence: 99%
“…A study by Bargmann et al (2014b) showed that the addition of HC initially inhibited seed germination of barley, but this effect was diminished after nine weeks, likely due to microbial decomposition. It was suggested that this decomposition was indirectly facilitated by the dissolved organic carbon (DOC) content of the HC, which stimulated microbial growth (Gronwald et al 2015;Hao et al 2018). The transient nature of this effect was also evinced by and Mukherjee et al (2016).…”
Section: Introductionmentioning
confidence: 99%